Profile of Speaking Instruction: A Case Study at English Language Instruction at Elementary Schools in Bandar Lampung - Akhmad Sutiyono (International Conference on Education and Language (ICEL), 2013)
This paper is part of the writer’s dissertation entitles, “The Development of Instructional Materials for Improving Students Speaking Skills at Elementary School.”This paper is aimed at describing English language instruction (ELI) at elementary schools in Bandar Lampung, especially on teaching speaking.  This paper is written based on the qualitative study conducted by the writer in elementary schools in Bandar Lampung. The study involved English teachers and students of elementary schools in Bandar Lampung. The data collecting method used in this study were: (1) classroom observation, (2) interview, (3) questionnaires, and (4) documentations.  The classroom observations were focused on the instructional features that the teachers employed in the classrooms and the students’ activities in learning speaking. He also observed the phenomena such as classroom interactions, the teacher’ activities, the students’ actibvities, the students’ motivation in learning English, and the problems encountered both by the teachers and students in developing students’ speaking skills. Questionnaires and interviews were used to know the problems encountered in teaching speaking at elementary schools. To know the actual problems encountered by students, the writer distributed questionnaires to students and interviewed them from different elementary schools in Bandar Lampung.The study shows that speaking instruction at English language instruction at elementary schools in Bandar Lampung has not been conducted well.  It happened because of some factors include: (1) lack of materials for speaking instruction, (2) the English teachers have lack of self confidence in using English when conducting instructional activities, (3) lack of students’ motivation to speak English, and (4) there is no speaking test for summative test.